Sistema logístico y planificación de inventarios en la unidad ejecutora 406 red de salud Ucayali Contamana 2024 - Huaman Maynas, Oscar Eli (2025)
This research aimed to determine the relationship between the logistics system and inventory planning in the Executive Unit 406 Ucayali Health Network Contamana 2024. Our research was basic, non-experimental design and correlational level, which had a total of 80 workers as a sample, who were surveyed through questionnaires. The results found showed us that the logistics system is considered regular, since sometimes the selection process for the acquisition of goods and services is carried out correctly, the warehouse is usually divided into specific zones or areas to facilitate its storage and handling; However, the Proof of Departure Order is always issued to the user area as part of the goods delivery process. Inventory planning is considered regular, with 29%. This is because, sometimes, appropriate decisions are made regarding the products that must be stored in the executing unit. The results of the correlation test showed a coefficient of 0.810, indicating a strong positive correlation between the logistics system and inventory planning in the entity. The statistical significance of 0.000, which is lower than the accepted threshold of 0.05, allowed corroboration of the research hypothesis.